Diagnostic criteria in 72 women with erosive vulvovaginal lichen planus. (26th May 2015) - Cheng, Harriet; Oakley, Amanda; Rowan, Darion; Lamont, Duncan
Abstract: Background: Erosive vulvovaginal lichen planus (EVLP) is a chronic, painful dermatosis affecting mucocutaneous sites. Clinicopathological diagnostic criteria have been described on the basis of expert consensus. The aim of this study was to review the presentation of EVLP, particularly assessing the frequency of suggested diagnostic criteria. Methods: Clinical signs, symptoms and histological features of women with a clinical diagnosis of EVLP were identified from clinical records and photographs. Results: In all, 72 women with an average age of 67 years were included. Pain or burning were documented in 66/72 cases (92%) and itch in 36 (50%). Clinical images showed well‐demarcated red shiny areas or erosions at the vaginal introitus (96%), scarring with loss of normal architecture (88%) and hyperkeratotic border and Wickham striae (46%). A total of 27 women had mucosal disease at another site (38%) and 24 had vaginal involvement (33%). Vulval histology was available for 45/72 cases (63%). The most prevalent histological finding was a band of inflammation with predominant lymphocytes (35/72, 49%). Overall, 97% of cases had at least three of nine suggested diagnostic criteria. Conclusions: The most frequent findings in women with EVLP were symptoms of pain or burning, well‐demarcated red shiny areas or erosions at the introitus and scarring with loss of architecture. Our findings support the recently described diagnostic criteria for EVLP.